Asesmen Klinis pada Remaja dengan Ketakutan terhadap Penilaian Negatif (Fear of Negative Evaluation) dalam Interaksi Sosial - Nabila Tasya Kadir; Nabila Nur Ainsya Syaus; Nadya Dinata Thamrin; Afifa Syahira Stion; Nur Asra Paputungan (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescence is a developmental stage that is vulnerable to the emergence of Fear of Negative Evaluation (FNE) in social interactions. This condition may affect adolescents’ ability to build social relationships and impact their psychological well-being. This study aims to examine clinical assessment procedures for adolescents with FNE and identify influencing factors as well as intervention strategies. A systematic literature review method was employed using data from Google Scholar with keywords related to adolescent social anxiety and clinical psychological assessment. A total of 24 scientific articles published between 2020–2026 were analyzed using thematic analysis. The findings indicate that FNE is associated with avoidance behavior, low self-esteem, loneliness, and increased risk of social anxiety and depression. Factors such as cyberbullying, social media use, social rejection, and self-image distortion contribute to its development. Integrated assessment using psychometric and projective instruments provides a more comprehensive psychological profile. Cognitive-based interventions, social support, self-compassion, and expressive approaches are effective in improving adolescents’ social adaptation.